Covalent Modification of the Transactivator Protein IE2-p86 of Human Cytomegalovirus by Conjugation to the Ubiquitin-Homologous Proteins SUMO-1 and hSMT3b - Hofmann, Heike (American Society for Microbiology, 2000)
The 86-kDa IE2 protein (IE2-p86) of human cytomegalovirus (HCMV) is a potent transactivator of viral as well as cellular promoters. Several lines of evidence indicate that this broad transactivation spectrum is mediated by protein-protein interactions. To identify novel cellular binding partners, we performed a yeast two-hybrid screen using a N-terminal deletion mutant of IE2-p86 comprising amino acids 135 to 579 as a bait. Here, we report the isolation of two ubiquitin-homologous proteins, SUMO-1 and hSMT3b, as well as their conjugating activity hUBC9 (human ubiquitin-conjugating enzyme 9) as specific interaction partners of HCMV IE2. The polypeptides SUMO-1 and hSMT3b have previously been shown to be covalently coupled to a subset of nuclear proteins such as the nuclear domain 10 (ND10) proteins PML and Sp100 in a manner analogous to ubiquitinylation, which we call SUMOylation. By Western blot analysis, we were able to show that the IE2-p86 protein can be partially converted to a 105-kDa isoform in a dose-dependent manner after cotransfection of an epitope-tagged SUMO-1. Immunoprecipitation experiments of the conjugated isoforms using denaturing conditions further confirmed the covalent coupling of SUMO-1 or hSMT3b to IE2-p86 both after transient transfection and after lytic infection of human primary fibroblasts. Moreover, we defined two modification sites within IE2, located in an immediate vicinity at amino acid positions 175 and 180, which appear to be used alternatively for coupling. By using a SUMOylation-defective mutant, we showed that the targeting of IE2-p86 to ND10 occurs independent of this modification. However, a strong reduction of IE2-mediated transactivation of two viral early promoters and a heterologous promoter was observed in cotransfection analysis with the SUMOylation-defective mutant. This suggests a functional relevance of covalent modification by ubiquitin-homologous proteins for IE2-mediated transactivation, possibly by providing an additional interaction motif for cellular cofactors.